Multi-model comparison of Swiss decarbonization scenarios - Florian Landis; Adriana Marcucci; Sebastian Rausch; Ramachandran Kannan; Lucas Bretschger (Swiss Journal of Economics and Statistics, 2019)
Collaborating under the Swiss Energy Modeling Platform (SEMP), five modeling teams (employing an energy systems model and four macroeconomic models with a focus on energy) have carried out a multi-model comparison to assess the economic and technological consequences of reaching emission reduction targets for 2050 in the context of Switzerland. We consider different designs of carbon taxes to compare their economic cost: economy-wide or sector-specific carbon taxes with or without an emission trading system (ETS) in place. All models find that the climate targets can be reached at modest welfare reductions of 0.15-0.37% (if targeting 1.5 tonnes of CO 2 per capita) or 0.24-0.48% (if targeting 1.0 tonnes per capita) compared to a business-as-usual scenario in which the emission level of 1.5 tonnes per capita is exceeded by 83-137%. In contradiction to the additional target of reducing Swiss electricity use, most models find it cost-effective to replace some of the energy supplied by fossil fuels by electricity and thus do not recommend a decrease in electricity use.Most models find that a uniform carbon tax is the most efficient instrument to achieve the emission reduction targets. Those models with a detailed representation of pre-existing mineral oil taxes find that in early periods of climate policy, taxing emission from transport fuels at lower rates than other emissions may be cost-efficient. This effect vanishes as the stringency of targets and thus CO 2 taxes increase over time.
Keywords: 330; Climate policy; Switzerland Model comparison; Energy system modeling; Computable general equilibrium; Cost-effectiveness